2003
DOI: 10.2135/cropsci2003.1610
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Partial Resistance to Phytophthora sojae in Soybean

Abstract: Partial resistance to Phytophthora sojae Kauffmann and Gerdemann in soybean [Glycine max (L.) Merr.] is expressed as a reduced level of root rot and is effective against all populations of the pathogen. The objective of this study was to identify simple sequence repeat (SSR) markers associated with putative quantitative trait loci (QTLs) for partial resistance to P. sojae in the soybean ‘Conrad’. Three recombinant inbred soybean populations, Conrad × ‘Sloan’, Conrad × ‘Harosoy’, and Conrad × ‘Williams’, were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 56 publications
(54 reference statements)
7
124
4
Order By: Relevance
“…A population of 316 F 9:11 RILs was phenotyped for resistance to P. sojae by means of the tray assay as described previously (Burnham et al, 2003;Lee et al, 2013a,b;Wang et al, 2010Wang et al, , 2012a. In brief, plants were grown in vermiculite (Perlite Vermiculite Packing Industries, Inc.) in the greenhouse for 7 d, and the roots were washed in tap water to remove vermiculite.…”
Section: Resistance To Phytophthora Sojae Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…A population of 316 F 9:11 RILs was phenotyped for resistance to P. sojae by means of the tray assay as described previously (Burnham et al, 2003;Lee et al, 2013a,b;Wang et al, 2010Wang et al, , 2012a. In brief, plants were grown in vermiculite (Perlite Vermiculite Packing Industries, Inc.) in the greenhouse for 7 d, and the roots were washed in tap water to remove vermiculite.…”
Section: Resistance To Phytophthora Sojae Assaymentioning
confidence: 99%
“…The soybean cultivar 'Conrad' (Fehr et al, 1989) has been identified as a source of resistance to P. sojae and F. graminearum (Burnham et al, 2003;Li et al, 2010;Ellis et al, 2012;Wang et al, 2010Wang et al, , 2012a, while the cultivar 'Sloan' (Bahrenfus and Fehr, 1980) is moderately to highly susceptible to these same pathogens (Ellis et al, 2012;Wang et al, 2010Wang et al, , 2012a. Both cultivars have similar levels of moderate susceptibility to Py.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…glycinea) and two viral resistance alleles, Rsv1 (resistance to Soybean mosaic virus) and Rpv1 (resistance to Peanut mottle virus) (Ashfield et al, 1998;Ashfield et al, 2004;Gore, 2000;Hayes et al, 2004;Koning et al, 2002;Schmittehener, 1999). A QTL for partial resistance to P. sojae was reported on MLG F between marker Satt252 and Satt423 (Burnham et al, 2003b) and QTL's conferring resistance to Meloidogyne javanica, M. arenaria, Heterodera glycines, and soybean sudden death syndrome (SDS) have been mapped on the MLG F (Concibido et al, 1994;Hnetkovsky et al, 1996;Tamulonis, et al, 1997a;Tamulonis et al, 1997b;Webb et al, 1995). Nutrient availability is a limiting factor for microbial growth and activity in agricultural soils, as a result plant pathogenic fungi and oomycetes propagules survive in soils in a state of exogenous dormancy or fungistasis (Lockwood, 1977).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Crosses between more diverse parents resulted in derived lines with greater values for grain yield (Table 1) and grain quality ( The SSR markers linked to the major QTL will be useful for marker-assisted selection in soybean-breeding programs (Funatsuki et al, 2005;Panthee et al, 2006). A set of SSR markers have been subjected to continuous development and utilization for high throughput molecular mapping in soybean (Akkaya et al, 1992(Akkaya et al, , 1995Narvel et al, 2000;Burnham et al, 2003;Shultz et al, 2007).…”
Section: Simple Sequence Repeats (Microsatellites)mentioning
confidence: 99%